Green Destinations as a Solution for Improving the Local Economy and Environmental Conservation - ANANTA, Ketut Prabha Yoga; WALUYO, Fahrel; SUDHARSANA, Komang Ray Tanaya; KARANG, Anak Agung Gde Danendra Warshana; SASTRAWAN, Kadek Dwiva (Journal Management and Hospitality, 2025)
The concept of green destination emerged as a solution to overcome the negative impact of tourism on the environment. This research analyzes the implementation of sustainable tourism through a literature study with a focus on four main pillars: carbon emission reduction, biodiversity preservation, sustainable waste management, and water resource conservation. The findings show that the success of a green destination depends on multi-stakeholder collaboration (government, local communities, industry, and tourists) and the implementation of strategies such as human resource capacity building, green policy incentives, and tourist education. Case studies from various regions in Indonesia such as Penglipuran Village, Komodo National Park, and Kampung Warna-Warni Jodipan prove that this approach can improve local economic welfare while preserving the environment. The main challenges faced are low environmental awareness and limited resources, but systematic solutions such as those outlined in this study can guide the development of sustainable tourism destinations in the future.